Effects of Transport Duration and Environmental Conditions in Winter or Summer on the Concentrations of Insulin-Like Growth Factors and Insulin-Like Growth Factor-Binding Proteins in the Plasma of Market-Weight Pigs - Wirthgen, Elisa; Goumon, Sébastien; Kunze, Martin; Walz, Christina; Spitschak, Marion; Tuchscherer, Armin; Brown, Jennifer; Höflich, Christine; Faucitano, Luigi; Hoeflich, Andreas (Frontiers in Endocrinology, 2018)
In previous work using market-weight pigs we had demonstrated that IGFs and IGFBPs are regulated during shipment characterized by changing conditions of stress due to loading or unloading, transportation, lairage, and slaughter. In addition we found in a previous study, that IGFBP-2 concentrations were lower in pigs transported for longer periods of time. Therefore we performed a more detailed study on the effects of transport duration and season on the plasma concentrations of IGFs and IGFBPs in adult pigs. EFor the study, xsanguination blood was collected from 240 market-weight barrows which were transported for 6, 12, or 18 h in summer or winter. IGF-I and -II were detected using commercial ELISAs whereas IGFBPs were quantified by quantitative Western ligand blotting. In addition established markers of stress and metabolism were studied in the animals. Plasma concentrations of IGFBP-3 were significantly reduced after 18 h of transport compared to shorter transport durations (6 and 12 h; p<0.05). The concentrations of IGF-I in plasma were higher (p<0.001) in pigs transported 12 h compared to shorter or longer durations. Season influenced plasma concentrations of IGFBP-3 and IGF-II (p<0.05 and p<0.01, respectively). Neither transport duration nor season had an effect on glucocorticoids, albumin, triglycerides, or glucose concentrations (p>0.05). However, low-density lipoprotein concentrations decreased after 18 h compared to 6 h of transport (p<0.05), whereas high-density lipoprotein concentrations were higher (p<0.05) in pigs transported for 12 or 18 h compared to those transported for only 6 h. Our findings indicate differential regulation of IGF-compounds in response to longer transport duration or seasonal changes and support current evidence of IGFs and IGFBPs as innovative animal-based indicators of psycho-social or metabolic stress in pigs.